Development of nanoemulsion for efficient brain parental delivery of cefuroxime: designs,characterizations,and pharmacokinetics - Harun, Siti Norhawani; Amin Nordin, Syafinaz; Abd Gani, Siti Salwa; Shamsuddin, Ahmad Fuad; Basri, Mahiran; Basri, Hamidon (Dove Medical Press, 2018)
Background and aim: Drugs that are effective against diseases in the central nervous system and reach the brain via blood must pass through the blood–brain barrier (BBB), a unique interface that protects against potential harmful molecules. This presents a major challenge in neuro-drug delivery. This study attempts to fabricate the cefuroxime-loaded nanoemulsion (CLN) to increase drug penetration into the brain when parenterally administered. Methods: The nanoemulsions were formulated using a high-pressure homogenization technique and were characterized for their physicochemical properties. Results: The characterizations revealed a particle size of 100.32±0.75 nm, polydispersity index of 0.18±0.01, zeta potential of -46.9±1.39 mV, viscosity of 1.24±0.34 cps, and osmolality of 285.33±0.58 mOsm/kg, indicating that the nanoemulsion has compatibility for parenteral application. CLN was physicochemically stable within 6 months of storage at 4°C, and the transmission electron microscopy revealed that the CLN droplets were almost spherical in shape. The in vitro release of CLN profile followed a sustained release pattern. The pharmacokinetic profile of CLN showed a significantly higher Cmax, area under the curve (AUC)0–t, prolonged half-life, and lower total plasma clearance, indicating that the systemic concentration of cefuroxime was higher in CLN-treated rats as compared to cefuroxime-free treated rats. A similar profile was obtained for the biodistribution of cefuroxime in the brain, in which CLN showed a significantly higher Cmax, AUC0–t, prolonged half-life, and lower clearance as compared to free cefuroxime solution. Conclusion: Overall, CLN showed excellent physicochemical properties, fulfilled the requirements for parenteral administration, and presented improved in vivo pharmacokinetic profile, which reflected its practical approach to enhance cefuroxime delivery to the brain.